Loneliness and Psychological Well Being on International Students of The Darmasiswa Program at Universitas Negeri Yogyakarta - Mawas Dwi Cahyadi (Psychological Research and Intervention, 2019)
This research aims to describe and find out the correlation between loneliness and the psychological well-being of international students of the Darmasiswa program at Yogyakarta State University. This research uses descriptive quantitative methods and data sources are obtained based on instruments that are distributed to 20 research subjects the international students. The research data were collected with the UCLA Loneliness Scale and Psychological Well Being Scale instruments which were then analyzed using SPSS 22.0 with the Pearson Product Moment correlation test. The results showed that there was a very weak negative relationship (r=-0.152) between loneliness and the psychological well-being of Darmasiswa students at Yogyakarta State University. Most research subjects have low levels of loneliness and moderate psychological well-being. There are two dimensions of psychological well-being that have the highest relationship with loneliness, namely environmental mastery (-0,338) and positive relationships with others (-0,299).